CD44 binding through the hemopexin-like domain is critical for its shedding by membrane-type 1 matrix metalloproteinase. - Suenaga, N; Mori, H; Itoh, Y; Seiki, M (2005)
Membrane-type 1 matrix metalloproteinase (MT1-MMP) is a potent modulator of pericellular environment through its proteolytic activity and promotes migration, invasion, and proliferation of tumor cells. During cell migration, MT1-MMP binds to CD44H, a major hyaluronan receptor, through the hemopexin-like (HPX) domain and localizes at the migration front. MT1-MMP is also responsible for shedding CD44H, which supports CD44H-mediated cell migration. In this study, we asked whether the binding of MT1-MMP to CD44H is a prerequisite step for the successive shedding. Deletion of the HPX domain deprived MT1-MMP of its shedding activity. Furthermore, disruption of the CD44H/MT1-MMP complex by overexpressing the HPX fragments resulted in inhibition of the shedding. Thus, the CD44H in the complex appears to be the direct substrate of MT1-MMP for shedding. Interestingly, other members of the MT-MMP family showed varied extents of CD44H shedding. Domain swapping between MT1-MMP and other MT-MMPs revealed that the ability of the HPX domains to bind CD44H is conserved among them. However, the shedding activity was different depending on the catalytic domains. The conserved binding ability of the HPX domains suggests that CD44H may act as a core molecule assembling multiple MT-MMPs on the cell surface.